Acute Management of Maxillofacial Trauma: A Review of Literature - Bijayalaxmi Panigrahi1 , Santosh Kumar Subudhi2 , Sthitaprajna Lenka2Shibasis Biswas1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Management of trauma has progressed dramatically over the past few decades thereby reducing mortalityin the golden hour. Challenges exist, however, one such region is maxillofacial injury in a patient withpolytrauma. Because of the regions close to the brain, cervical spine and airway, serious injuries to themaxillofacial area may complicate the early treatment of a trauma patient. In case of maxillofacial injuries, thenormal procedures of airway respiration and circulation (ABC) management are also changed or augmentedby other approaches. In an often-challenging situation these modifications have their own difficulties andpitfalls.